INTERVENSI TUANKU TERKAIT PRAKTEK NIKAH SIRRI DI NAGARI KURAI TAJI PARIAMAN - Ashabul Fadhli; Fathurrahmi Fathurrahmi (Kafa`ah: Journal of Gender Studies, 2016)
One form of marriage that is not justified in view of Islamic law is a marriage that is conducted secretly (sir) or in this case called by Siri marriage. The marriage is not considered perfect, when it has not been published and equipped with the testament. The marriage that has been overshadowed by the elements or attempt to conceal, classified in prohibited marriage. In order not to fall into this category, then the solution is to announce. Qualitative approach was used where the data collected from Ungku and some people in Nagari Kurai Taji Pariaman. This descriptive research was analyzed using a normative-juridical-socio approach. The study found that there was clear goal to realize an ideal household life and have the force of law. But a legal guarantee by the state through the legal framework was not implemented in Nagari Kurai Taji Pariaman, West Sumatra. The study also discovered that the groom and bride were married Siri by the religious leaders (Ungku) from local society; not by Qadhi as the authorities designated by law.